2010
DOI: 10.1243/09544062jmes1681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interfacial debonding on the elastoplastic response of unidirectional silicon carbide—titanium composites

Abstract: A three-dimensional micromechanics-based analytical model is presented to investigate the effects of initiation and propagation of interface damage on the elastoplastic behaviour of unidirectional SiC-Ti metal matrix composites (MMCs) subjected to off-axis loading. Temperature-dependent properties are considered for the matrix. Manufacturing process thermal residual stress (RS) is also included in the model. The selected representative volume element consists of r × c unit cells in which a quarter of the fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Finite element method (FEM) and analytical approaches are used for micromechanical modeling of two-phase composites and to obtain the effective properties of such materials. 121 These analytical methods and FEM could predict the overall behaviors of two-phase composites with reasonable accuracy. An analytical micromechanical model based on unit-cell method was presented 20 to predict the behavior of fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finite element method (FEM) and analytical approaches are used for micromechanical modeling of two-phase composites and to obtain the effective properties of such materials. 121 These analytical methods and FEM could predict the overall behaviors of two-phase composites with reasonable accuracy. An analytical micromechanical model based on unit-cell method was presented 20 to predict the behavior of fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 94%
“…The preliminary analytical model was later extended and modified to investigate the effects of initiation and propagation of interface damage on the elastoplastic behaviour of unidirectional SiC/Ti metal matrix composites. 21 The method is called Simplified Unit Cell (SUC) in the literature. 21 In some composites, interphases between the reinforcement phase and the matrix material have a significant effect on the thermo-mechanical behavior of such composite materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of the SUC method is its ability to give closed-form solutions to evaluate the composite material response to shear and normal loadings (Falahatgar et al, 2009; Mahmoodi et al, 2010; Sayyidmousavi et al, 2015). Numerous research studies have revealed the validity of the model to predict the overall behavior of conventional composites (Falahatgar et al, 2009; Mahmoodi and Aghdam, 2011; Mahmoodi et al, 2010; Sayyidmousavi et al, 2015). The SUC micromechanical model was later extended by Ansari and Hassanzadeh-Aghdam (2016a, 2016b) to calculate the linear and non-linear viscoelastic properties of CNT-reinforced polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…This article deals with the thermal expansion behavior of SiO 2 –SMP nanocomposites using the SUC micromechanics model (Ansari et al, 2016a; Ansari and Hassanzadeh-Aghdam, 2016a, 2016b; Falahatgar et al, 2009; Hassanzadeh-Aghdam et al, 2018; Mahmoodi and Aghdam, 2011b; Mahmoodi et al, 2010a, 2010b). The rest of the article is organized as follows.…”
Section: Introductionmentioning
confidence: 99%